NanoPhil Technologies InstaClean self-cleaning exterior paint - Felicio, Geraldine Mae P.; Reyes, Vincent Augustine F.; Ueno, Rani Aiko Marie P.; Yupingkun, Lancelot C. (College of Engineering, 2013)
This study establishes the feasibility of InstaClean, a nanotechnology-based self-cleaning exterior wall paint InstaClean is the flagship project of NanoPhil Technologies, a corporation to be established with the aim of pioneering the manufacture of nanotechnology-based materials in the Philippines. InstaClean, the result of a study by the Department of Science and Technology (DOST), is an exterior wall paint that uses a mix of two types of nanoparticles, titanium dioxide and silica. These compounds essentially convert the painted walls into hydrophobic surfaces which allow water to carry away the dust and lipophilic dirt which settle on the wall, making the wall paint self-cleaning. This inherent self-cleaning ability is what makes InstaClean stand out to consumers, as it will be the first local self-cleaning paint to be introduced to the market. InstaClean is also notable, however, for its pioneering use of silica from rice hull ash, an agricultural waste in the Philippines. The process of converting silica to rice hull ash has not yet been introduced to the country. This process allows InstaClean to be manufactured at a much lower cost, allowing the product to be sold at a price that is lower than the current going price of self-cleaning paints currently available in the foreign market. The marketing of InstaClean is primarily directed towards the construction industry's private sector. This contractors, developers, architectural firms, dealers, and owners of private structures. The market is also expanded to public sector construction projects, by marketing to the private contractors who usually bid on these projects. Marketing efforts primarily include joining trade conventions, partnership building, credentialing, guerilla marketing activities, and mass media exposure. These marketing efforts are expected to yield the demand forecasts and predicted market shares shown in the table below. Revenue is computed at a price point of Php 900, the price determined to best communicate the premium yet affordable quality positioning of InstaClean. In order to accommodate this demand, NanoPhil Technologies will outsource manufacturing in the first two years, and then begin in-house production in Year 3. By Year 5, NanoPhil Technologies is expected to have two production lines for the entire InstaClean production process (mixing, grinding, and filling), with a total production capacity of 123,000 gallons per year. The organization size is expected to grow as production grows. Starting with a lean organization in 2014, the company will grow to six functional departments by 2015. To fund NanoPhil Technologies' operations, two major cash injections will be required. Owners' equity of Php 2.35M is needed in 2014 in order to fund the incorporation of the company and its Year 1 operations. A Php 7.7M investment is then required in 2016 to fund the company's expansion. Php 2M of this investment can be loaned from the SET-UP program of the DOST, while the remaining amount can be loaned from financial institutions. These investments, however, are expected to yield positive returns. The project is expected to yield a Net Present Value (NPV) of Php 16.1M, and an Internal Rate of Return (IRR) of 143%. Net Income for the first five years of the company's operations are shown below (in millions of pesos): A socio-profitability analysis of the project also shows that it is highly beneficial to society. There is a wide range of benefits, some of which include: consumer savings from reduced cleaning and repainting; conversion of rice hull ash from agricultural waste to a source of revenue for rice farmers; and foreign exchange savings. Overall, a Benefit-Cost Ratio of 4.66 is expected from the project. Thus, the study establishes the following: A steadily growing market can be found to support the production of InstaClean. InstaClean's production requirements can be supported. InstaClean will yield a high return on investment. There are major social benefits to the realization of InstaClean in the market. Overall, It can therefore be seen that the production of InstaClean is commercially,technically, and financially feasible.